PENGEMBANGAN MODUL AJAR MENULIS TEKS DESKRIPSI DENGAN MODEL DISCOVERY LEARNING PADA SISWA KELAS VII SMP NEGERI 02 PONTIANAK - Rahayu, Dian; Priyadi, Antonius Totok; Sanulita, Henny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study addressed the problem of many teachers lacking understanding of module structure and insufficient reference materials, leading to suboptimal educational modules. Limited media usage also caused boredom and low learning outcomes. The study aimed to develop an educational module, assess its feasibility, test media effectiveness, and determine the module"™s practical viability. By using the ADDIE model with a research and development (RD) approach, this study involved students of class VII C of SMP Negeri 02 Pontianak. Data were collected through testing and analyzed with validity tests, normality tests, t-tests and N-gain tests. The results showed a validation rate of 97.64% by material experts, 94% by media experts, and 93.84% by language experts, with values that were normally distributed in the normality test. The t-test showed a significant influence on student learning outcomes. In the small group test, the average pre-test and post-test scores were 65.77 and 85.55, respectively, resulting in an N-gain of 0.6024 (moderate category). In the large group test, a mean of 64.66 and 86.73 was obtained with an N-gain of 0.6110 (moderate category). These results confirm the media"™s effectiveness in enhancing learning outcomes. The module"™s usability scored 73 points, or 97%, placing it in the "very useful" category.